STUDIES ON THE IMPACT OF MEDICINAL PLANTS IN RELATION TO MALARIA VECTOR CONTROL AGAINST ANOPHELES STEPHENSI - Bharani, Bharanitharan; N, Muthulingam; S, Senthilmurugan; A, Dhanasekaran; A, Jeyasankar; Sawicka, Barbara (Innoriginal: International Journal of Sciences, 2018)
The present study phytochemical screening and mosquitocidal activity of three different medicinal plants, Sesamum indicum, Pungamia pinnata, and Croton bonplandionum extracts. The methanol extract of leaf samples were used for the phytochemical analysis to find out the phytochemical constituents in the plants. The main objective of the research work was check the presence or absence of the phytochemical chemicals in all the selected medicinal plants. Phytochemical analysis of these plants confirm the presence of various phytochemicals like alkaloids, flavonoids, saponins, steroids, tannins, terpenoids, tri-terpenoids, anthraquinones, amino acid, phenol, glycosides, carbohydrate, protein and phytosteroids. The highest larvicidal activity of S. indicum methanol extract with LC50/LC95 values were 108.55/230.57 ppm, followed by P. pinnata were 143.59/305.52 ppm, and C. bonplandionum were 154.51/319.01 ppm, respectively. Further, maximum repellent activity of methanol extract showing 100% protection up to 160 min was tested against An. stephensi. However, much scope for further systematic research in screening Tamilnadu medicinal plants for these phytochemicals and assessing their potential in protecting against different types of mosquito diseases. Â  Keywords: Sesamum indicum, Pungamia pinnata, and Croton bonplandionum, phytochemical, mosquitocidal